DISPARITY OF COURT DECISIONS IN THE CASES OF PASSENGER NOT ACCOUNTING FOR THE REASON OF AIRCRAFT CAPACITY - HARIDDIN, MUHAMMAD; ALAUDDIN, RUSDIN; RUMKEL, NAM (Awang Long Law Review, 2020)
One of the cases where passengers were not transported due to an overcapacity of the aircraft (overseat) occurred on the Lion Air Manado - Jakarta flight with flight number JT 743 on 19 October 2011, in connection with this case there were two passengers who objected and suffered losses for this incident, and filed a civil suit to the Central Jakarta District Court for the settlement process with Decision Number: 42/Pdt.G/2012/PN.JKT. PST. and Decision Number: 260/Pdt.G/2014/PN.JKT.PST. This paper will discuss more deeply the basis for judges' considerations so that there are disparities in court decisions. The type of research used is juridical normative, with a statutory approach and a case approach. The data collected is then analyzed qualitatively. The results showed that District Court Decision Number 260/PDT.G/2014/PN.JKT.PST where the Plaintiff filed a lawsuit for act against the law but the Judge decided that the Defendant was guilty of default for the act of not carrying passengers on the grounds of aircraft capacity, this was related to the application of the passive judge principle and the ultra petitum partium principle which had broad meaning in good faith by the judge, then on District Court Decision Number 42/PDT.G/2012/PN.JKT.PST the judge decided that the Defendant was guilty of committing an unlawful act in terms of the absence of passengers on the grounds that the aircraft's capacity was in accordance with the Plaintiff's claim.